3D Interactions between Virtual Worlds and Real Life in an E-Learning Community. (9th May 2011) - Lucke, Ulrike; Zender, Raphael
Abstract : Virtual worlds became an appealing and fascinating component of today's internet. In particular, the number of educational providers that see a potential for E-Learning in such new platforms increases. Unfortunately, most of the environments and processes implemented up to now do not exceed a virtual modelling of real-world scenarios. In particular, this paper shows that Second Life can be more than just another learning platform. A flexible and bidirectional link between the reality and the virtual world enables synchronous and seamless interaction between users and devices across both worlds. The primary advantages of this interconnection are a spatial extension of face-to-face and online learning scenarios and a closer relationship between virtual learners and the real world.